2018
DOI: 10.1523/jneurosci.0154-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Repression of MYRF Self-Cleavage and Activity in Oligodendrocyte Differentiation by TMEM98 Protein

Abstract: Myelin sheath formed by oligodendrocytes (OLs) is essential for the rapid propagation of action potentials in the vertebrate CNS. Myelin regulatory factor (MYRF) is one of the critical factors that control OL differentiation and myelin maintenance. Previous studies showed that MYRF is a membrane-bound transcription factor associated with the endoplasmic reticulum (ER). After self-cleavage, the N-fragment of MYRF is released from the ER and translocated into the nucleus where it functions as a transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…It belongs to the small family of Ig fold transcription factors with an Ndt80 DNA‐binding domain in its aminoterminal half. The carboxyterminal half of the protein contains a transmembrane domain and anchors the newly synthesized protein in the membrane of the endoplasmic reticulum where it forms trimers and associates with Tmem98 (Huang et al, ). These trimers undergo autoproteolysis, possibly influenced by Tmem98, and release a trimer of aminoterminal Myrf fragments that enters the nucleus and acts as a transcription factor (Bujalka et al, ).…”
Section: Transcriptional Control Of Central Myelination By Stage‐specmentioning
confidence: 99%
See 1 more Smart Citation
“…It belongs to the small family of Ig fold transcription factors with an Ndt80 DNA‐binding domain in its aminoterminal half. The carboxyterminal half of the protein contains a transmembrane domain and anchors the newly synthesized protein in the membrane of the endoplasmic reticulum where it forms trimers and associates with Tmem98 (Huang et al, ). These trimers undergo autoproteolysis, possibly influenced by Tmem98, and release a trimer of aminoterminal Myrf fragments that enters the nucleus and acts as a transcription factor (Bujalka et al, ).…”
Section: Transcriptional Control Of Central Myelination By Stage‐specmentioning
confidence: 99%
“…Myrf is a somewhat unusual transcription factor (Emery, 2010). It Tmem98 (Huang et al, 2018). These trimers undergo autoproteolysis, possibly influenced by Tmem98, and release a trimer of aminoterminal Myrf fragments that enters the nucleus and acts as a transcription factor (Bujalka et al, 2013).…”
Section: Transcriptional Control Of Central Myelination By Stage-spmentioning
confidence: 99%
“…It has also been reported to be able to promote the differentiation of T helper 1 cells and to be involved in the invasion and migration of lung cancer cells 49, 53 . Recently it has been reported that TMEM98 interacts with MYRF and prevents its autocatalytic cleavage 54 . In relation to human disease two TMEM98 missense mutations, A193P and H196P, have been reported to be associated with dominant nanophthalmos 12, 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The two missense mutations that are associated with nanophthalmos introduce a proline in the middle of the final α-helix of the protein which would likely lead to disruption of the secondary structure of the protein 58 . The recent finding that TMEM98 binds to and prevents the self-cleavage of the oligodendrocyte transcription factor MYRF 54 (also highly expressed in the RPE; http://www.biogps.org) will perhaps lead to a mechanistic explanation, although the part of TMEM98 that binds to MYRF was mapped to the N-terminal 88 amino acids and a region between 55-152 amino acids was shown to be required for the cleavage inhibition. As the nanophthalmos patient-specific missense mutations are more C-terminal their effect on this reported interaction will be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…In situ RNA hybridization was performed as described by Schaeren-Wiemers and Gerfin-Moser (1993) with minor modifications. Western blotting was as described previously (Huang et al, 2018).…”
Section: Micementioning
confidence: 99%